London calling (or cooling?): Feature theory, phonetic variation, and phonological change - Uffmann, Christian (Yearbook of the Poznan Linguistic Meeting, 2021)
This article looks at the ongoing merger of /uː/ or /ɔː/ before tautosyllabic /l/, that is, words like call(ing) and cool(ing) in London English, the reasons for this merger and how it can be captured formally. It argues that the merger is the end point of a chain of phonological consequences of a phonetic process, the gradient fronting of /uː/, which leads to a reorganisation of the vowel system. The merger can thus only be understood by looking at the properties of London (Cockney) phonology and ongoing changes in this system. On the theoretical level, this article argues that underspecification in feature theory is crucial to understand the interaction between phonetic variation and phonological change, arguing that the vowel shifts in London English start out as phonetic changes along dimensions that are featurally underspecified. Underspecification thus provides a crucial link between phonological categories and phonetic gradience.